Travailler pour son « temps de repos » ? - Fanny Vincent (Temporalités)
Originally programmed as an exception in the law, working 12 hour shifts has been expanding in the public hospital sector for several years now, often at the behest of care workers themselves, and more and more services and professions are concerned by the phenomenon. Far from being marginal, the 12 hour shift seems today to represent a way for stressed care workers to claim the right to rest and take control of their own time.Taking off from an ethnographic survey carried out for an ongoing thesis in the services of several hospitals, and about forty interviews, this article analyses how care workers use and take advantage of the 12-hour system in terms of what they feel it offers with respect to their social time. It thus suggests interpreting care workers’ investment in the 12-hour system as a means toward social emancipation, in that it appears to them – compared to the other sorts of systems such as the 8-hour shift – as a chance to find a balance between their time at work and time off-work, and to regulate the place that work occupies in their existence. In that sense, and given the mainly female composition of the paramedical population, the article studies in particular the significance of the time liberated by the 12-hour system in the light of motherhood.